Spatially explicit economic model for unlocking sustainable forest management in a frontier of the colombian amazon - Adolfo Andres Hincapie Garcia (2017)
Although the role of logging and timber trade as drivers of tropical forest degradation has been widely discussed, it is not a straightforward story to be understood. Currently, there is little effort to include the customary forest users and their subsistence economy within the timber trade analysis. They have been discredited by a complicated history of illegality, informality, low environmental liability, and little effect on poverty alleviation. The purpose of this study is to explain the economic value of the timber trade (volumes, incomes, and stumpage) in two distinct ways; first, to understand its role in Colombian forest losses; and second, its role in possible solutions for reaching sustainable management, ecological, economic, and social of the Colombian Amazon forest. We construct a spatial econometric model based on residual analysis to compute forest revenue using Dinamica-EGO. Our model uses data from 26 interviews with actors living along the Caquetá, Putumayo and Amazonas departments in the south of the Colombian Amazon; official government data of legal logging reported in the National Forest Information System (SNIF) and opened geographical information sources. We estimate values for different economic parameters, as well as calculate the present forest value for two wood types, hardwood and softwood, and two land property regimes (public and private). Our results show that indigenous lands and farmer titled areas during the last 20 years have an average of US$ 22.4 ± 8.7/m3 for hardwoods. Meanwhile, the economic value for softwoods is in average US$ 6.4 ± 3.5/m3. The stumpage volume under a Reduced Impact Logging (RIL) scenario can be between 0.6 m3/ha/year (about 18 m3/ha in a cut cycle of 30 years), with net income around 52 and 72 US$/ha/year for hardwoods and 28 US$/ha/year for softwood. These values represent a challenge for sustainable forest management, particularly the values close to cero because they impoverish the value of the forest. This can therefore, incentivize illegality, forest degradation, and deforestation by changing the land use; neither reduce poverty in remote areas that still have timber potential but are non-utilized yet. Overall, this study provides evidence to unlock the economic value of sustainable forest management in the current context of growing demand for a sustainable market as REDD+.